Hubungan Interaksi Sosial, Kepercayaan Diri Dengan Harga Diri (Self Esteem) Anak Jalanan di Kabupaten Banyumas - Vatin Ashari Rahmawati; Sodikin - Sodikin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To identify the correlation between social interaction, self-confidence and self-esteem on street adolescence in Banyumas Regency. Method: This is analytic descriptive research using a cross-sectional approach. The research population is street adolescence in Banyumas Regency. The research sample consists of 57 respondents were taken through accidental sampling. Result: The respondents characteristic based on gender consists of a male, 41 (71.9%) and female, 16 (28.1%). The average respondents are aged 16 years old, the minimum age is 11 and the maximum age is 20 years old. The educational level of most respondents is junior high school, 32 (56.1%). It is found that there are 46 respondents (80.7%) having low self-esteem and 11 respondents (19.3%) having high self-esteem. There are 27 respondents (47.4%) having good social interaction and 30 respondents (52.6%) having bad social interaction. Moreover, there are 14 respondents (24.6%) having high self-confidence and 43 respondents (75.4%) having low self-confidence. Based on the bivariate analysis result, it is obtained that the significance level of social interaction is p=0.013 (0.0130.05) and self-confidence is p=0.029 (0.0290,05). Conclusion: There is a correlation between social interaction and self-confidence with self-esteem on street adolescence in Banyumas Regency